Upaya Peningkatan Fasilitas Wisata di Desa Wisata Dayeuhkolot, Kecamatan Sagalaherang, Kabupaten Subang - Syafganti, Imam; Anggraini, Asterina; Safitry, Tantri Sari; M. Iqbal Katik RE; Heri Setyawan; Djuni Akbar (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Jakarta, 2025)
Modern lifestyle trends have significantly increased public interest in travel, driving a rise in tourist visits to both regional and international destinations. This growing demand has prompted the development of new tourism alternatives, including tourism village programs. One example is Dayeuhkolot Tourism Village, located in Sagalaherang District, Subang Regency, which offers various natural and cultural attractions such as scenic landscapes, local wisdom, and cultural diversity. Despite its promising potential, the tourism development of Dayeuhkolot Village remains underdeveloped, particularly in terms of infrastructure and digital promotion. In response, the Applied Bachelor of MICE (Meetings, Incentives, Conventions, and Exhibitions) Study Program Politeknik Negeri Jakarta carried out a community service initiative aimed at enhancing the village's digital marketing capacity. The program focused on designing and installing digital signage to promote the village and increase its visibility to a broader audience. Activities included socialization, workshops, focus group discussions, and practical training sessions, supported by the provision of digital signage infrastructure. As a result, local stakeholders—especially tourism managers—showed improved understanding and skills in utilizing digital marketing tools. The installed signage attracted community attention and was seen as a valuable asset for promoting tourism sustainably. The village head acknowledged the impact of the initiative, highlighting its role in supporting long-term tourism development. Overall, the program contributed meaningfully to the empowerment of the tourism village through digital innovation, enabling more effective promotion strategies and reinforcing the village’s potential as an attractive and sustainable tourist destination.Keywords: facility, tourism village, digital advertisement, digital signage Saat ini, gaya hidup masyarakat modern mendorong peningkatan kunjungan wisatawan ke berbagai pilihan tempat wisata baik di lingkup regional maupun internasional. Meningkatnya kebutuhan masyarakat tersebut menjadi salah satu faktor pendorong munculnya banyak tempat wisata baru, salah satunya dalam bentuk program desa wisata. Wilayah Subang diketahui telah membuat program desa wisata edukasi pada beberapa desa di wilayahnya seperti salah satunya Desa Wisata Dayeuhkolot, Kecamatan Sagalaherang, Kabupaten Subang. Desa wisata Dayeuhkolot memiliki Daerah Tujuan Wisata (DTW) alam dan budaya yang menarik, termasuk keindahan alam, kearifan lokal, dan keragaman budaya. Namun, meskipun potensinya besar, perkembangan pariwisata di Desa Wisata Dayeuhkolot masih belum maksimal. Terutama dalam hal peningkatan fasilitas desa wisata berbentuk pengembangan infrastruktur wisata. Pengabdian masyarakat yang merupakan kegiatan rutinitas Program Studi Sarjana Terapan MICE bertujuan untuk membantu pengelola desa wisata dalam melakukan pemasaran digital untuk desa wisata Dayeuhkolot, terutama dalam pembuatan perangkat digital signage untuk membantu memasarkan desa wisata Dayeuhkolot. Peningkatan ini dilaksanakan dengan pembekalan secara teori dan praktik serta memberikan bantuan fasilitas agar mampu menunjang kegiatan pembuatan program desa wisata Dayeuhkolot. Metode peningkatan diberikan menggunakan sosialisasi, workshop, forum group discussion, dan pemasangan digital signage. Kepala Desa Dayeuhkolot menyampaikan bahwa workshop terkait pemasaran digital dan pemasangan digital signage sangat bermanfaat dalam pengelolaan desa wisata Dayeuhkolot secara berkelanjutan. Kata kunci: fasilitas, desa wisata, pemasaran digital, digital signage